STRESS PERSONALITY RELATIONSHIP OF IT PROFESSIONALS IN TRIVANDRUM CITY - Sivakami S. and Rathiha R
The present study focuses on the personal factors, that causes stress among Information Technology professionals working in Trivandrum city. 300 responses were received and included. Mean and Multiple discriminant analusis have been used to analyse the collected data. The personal factors of stress are grouped as individual factors and dependent factors. Male professionals are stressed more with individual stressors and female are stressed more with dependent stressors.